Sucessão familiar na bovinocultura de leite em Rio Bonito do Iguaçu-PR - Schmitt, Darlan (2019)
The problems associated to succession in family agriculture are increasing, much due to the large gap of the rural population living in countryside, compromising the continuity of agricultural activities. Among these activities, an of fundamental importance to small properties is dairy cattle, by providing enforcement in small territorial extensions and generating a determinant monthly source of income to manage the establishment. Knowing the relevance of this subject the present work visited 60 properties in the county of Rio Bonito do Iguaçu, dedicated to milk production where interviews were conducted with the objective of evaluating family succession at dairy cattle. So, an evident aging of the progenitors where 48.27% of those aged 50 years or more. Still, of all properties only 28.33% had young people between 16 to 29 years residing. Among the topics mentioned as youth outgrowers was identified mainly related issues to leisure, remuneration, education, and painful work with the dairy cattle. It was also found, as a widespread form, a lack of family dialogue regarding succession in the property of which there was only one case where the succession was constantly discussed and there was a clear definition of the future of property. Lastly, it can be determined that a large proportion of producers judged that bovine farming has a relevant influence on the issues of young people's exodus mainly due to the working conditions, which were considered to be laborious.